Analysis of Code Switching and Code Mixing Translation Quality in Yowis Ben Film Structure - Arina Swandani; M.R. Nababan; Riyadi Santosa (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This research aims to: 1) identifying type and function of code switching and code mixing in Yowis Ben (2018) and Yowis Ben 2 (2019) film structure, and 2) determining translation quality of code switching and code mixing Javanese-Indonesian into English subtitles for Yowis Ben (2018) and Yowis Ben 2 (2019) films. Primary data in this study consists of two; linguistic data and translation data. Linguistic data was obtained through content analysis and translation data was obtained through FGD (Forum Group Discussion). The results show that there are two kinds of code switching and three kinds of code mixing found in the films. Furthermore, there are 14 functions of code switching and code mixing used in the films. In translating code switching and code mixing, the translator used several techniques, including neutralization, modulation, paraphrasing, transposition, implicitation, explicitation, compensation, and description. From the results, the researcher found that most of the data are translated less accurate. However, the acceptability and readability aspects are in high level.